Trivelpiece-gould modes of waveguide partially filled with non-neutral plasma. Part 2 - Yeliseyev, Yu.N. (Problems of Atomic Science and Technology, 2023)
The frequency spectra of electron eigenmodes with the azimuthal number m = 1 of a waveguide partially filled with non-neutral plasma are determined numerically within the entire allowable range of electron densities and magnetic field strengths, for various values of the degree of charge neutralization and finite values of the longitudinal wave vector. Частотний спектр власних електронних мод з азимутальним числом m = 1, визначений чисельно для хвилеводу, частково заповненого зарядженою плазмою. Розрахунки виконані в межах усього допустимого діапазону густини електронів і напруженостей магнітного поля для різних значень ступеня зарядової нейтралізації і поздовжнього хвилевого вектора.